Strategi Segmenting, Targeting dan Positioning Pemasaran Beras Merah Organik Jatiluwih Bali di Provinsi Bali - DEWI, NI PUTU AYU YULIA; ANTARA, MADE; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.4, Oktober 2017, 2017)
Segmenting, Targeting, and Positioning Strategies of Marketing Jatiluwih Organic Brown Rice in Bali Province A company cannot serve all consumers in a vast market. Therefore, if the company wishes to be in the market and win a competition, it must seek a strategy that can understand consumers and competitors. This study aimed to determine the market segment (segmenting), target market (targeting) and market position (positioning) of organic red rice products of Jatiluwih Bali. The technique of determining samples used accidental non-probabilitiy random sampling method. Segmenting and targeting were done using cluster analysis and crosstab analysis tools. Positioning used Multi dimensional scaling and Corespondence analysis. The results of this study showed that there were 3 segments, with percentage of Segment-1 (49%), Segment-2 (31%) and Segment-3 (20%). Based on the market appeal, potential target market was segment-3. Product positioning based on MDS analysis tool, Jatiluwih rice product was not in any quadrant, so it showed no resemblance to the competitor's product. Positioning based on CA analysis, organic red rice products Jatiluwih Bali had advantages in health attributes, packaging and aroma. Suggestions that can be made are that the company should implement strategies to increase sales by maintaining or increasing the attributes of excellence, increasing price discounts and maintaining quality, developing promotional activities and diversification of processed red rice products.